Seat racing and crew selection (Rowing Biomechanics Newsletter, 2013)
Seat racing is quite a popular method of crews selection for big boats. How objective is the seat racing? This question is very important, because it may define an athlete`s carrier. Here the authors will give some recommendations and outline common mistakes.